Preliminary studies on landscape ecological structure of fragmented loess grasslands on the Zsolca Mounds (Felsőzsolca, Hungary) - Novák, Tibor J.; Nyilas, István; Tóth, Csaba (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
Prehistoric mounds on the Hungarian Great Plain function often as refuges for relict loess steppe vegetation and fauna. The Mounds in Felsőzsolca (Felsőzsolca, Borsod-Abaúj-Zemplén County, Northern Hungary) is one representative of them, covered by a loess grassland fragment in extnesion of 0,8 ha, surrounded by agricultural areas, well documented from floristical point of view. Less studied and analysed are the actual vegetation dynamics as result of their isolated location, small extension, and numerous and frequent disturbances (pedoturbation caused by mammals, fire and invasive species). With detailed soil, vegetation and faunistic field survey we attempted to describe the most relevant actual processes of these very valuable grassland fragments from conservational point of view. Vegetation were sampled in 28 1×1 m quadrats, ordered in transects by distance from the edge. Presence of 104 higher plant species and a significant edge effect in the outlying sections (until 3 m) were established. It could be characterized by a significant lower naturalness value, different plant composition, presence of weed and ruderal species such as Arctium lappa, Artemisia vulgaris, Atriplex patula since most of specialists (Salvia pratensis, Pulsatilla spp., Inula hirta, Aster amellus, Dianthus pontederae) were absent in the edge. The Zsolca Mounds take up a relatively small area as regarding the fauna, but according to the research we have done so far, many protected species can be found here. The anthropogenic mounds partly form a very dry, sunny and warm habitat for the fauna (on the southern side) while the northern side of the mounds is of higher biodiversity, due to the dense vegetation and balanced water supplies.